2022
DOI: 10.1097/rlu.0000000000004194
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Distributed Multi-institutional PET Image Segmentation Using a Federated Deep Learning Framework

Abstract: PurposeThe generalizability and trustworthiness of deep learning (DL)–based algorithms depend on the size and heterogeneity of training datasets. However, because of patient privacy concerns and ethical and legal issues, sharing medical images between different centers is restricted. Our objective is to build a federated DL-based framework for PET image segmentation utilizing a multicentric dataset and to compare its performance with the centralized DL approach.MethodsPET images from 405 head and neck cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…Building a generalizable and robust model requires a large dataset, while privacy concerns could be addressed by FL approaches without sacrificing models’ performance. In a more recent study, Shiri et al [ 76 ] proposed a FL based multi-institutional PET image segmentation framework on head and neck studies. They enrolled 404 patients from eight different centers and reported that FL-based algorithms outperformed CB and achieved similar performance as the CZ approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building a generalizable and robust model requires a large dataset, while privacy concerns could be addressed by FL approaches without sacrificing models’ performance. In a more recent study, Shiri et al [ 76 ] proposed a FL based multi-institutional PET image segmentation framework on head and neck studies. They enrolled 404 patients from eight different centers and reported that FL-based algorithms outperformed CB and achieved similar performance as the CZ approach.…”
Section: Discussionmentioning
confidence: 99%
“…This study inherently bears a number of limitations. The implementation of all models was performed on a server using different GPUs where the different nodes were considered as centers similar to previous FL studies [ 35 , 36 , 54 – 59 , 74 , 76 ]. The challenges of FL, such as local computer capacity, and communication bottleneck between centers and local server should be considered in the real clinical scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our dataset was obtained from one institute which undermines the robustness of the findings. Further studies might gather larger and diverse dataset obtained from multiple institutes with different image acquisition parameters and patients’ ethnicity to improve the reproducibility of the models [ 51 ]. However, for proof-of-concept, this study contained enough patients.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will aim to further improve the proposed method by adding more Conv layers and testing different loss functions. Although a dataset of 57 cervical patients was used in this study, increasing the training dataset would result in a model with improved accuracy and generalizability by using data augmentation [ 57 ] and decentralize federated learning [ 58 ] approaches. Another suggestion would be the use of more structure contours to take into account more anatomical considerations.…”
Section: Discussionmentioning
confidence: 99%